2017
DOI: 10.1103/physrevb.95.180409
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast magnetic switching of GdFeCo with electronic heat currents

Abstract: We report the magnetic response of Pt/Au/GdFeCo trilayers to optical irradiation of the Pt surface. For bilayers with Au thickness greater than 50 nm, the great majority of energy is absorbed by the Pt layer, creating an initial temperature differential of thousands of Kelvin between the Pt/Au layers and the GdFeCo layer.The resulting electronic heat current across the metal multilayer lasts for several picoseconds with energy flux in excess of 2 TW m -2 and provides sufficient heating to the GdFeCo electrons … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 35 publications
2
37
0
Order By: Relevance
“…Moreover, by replacing the [Co/Pt] layer by a GdFeCo layer, GdFeCo magnetization switching using ultrafast hot electron pulses and without direct light interaction was demonstrated [124]. These findings confirm the work reported by Wilson et al [125]. Therefore, switching the magnetization at the picosecond timescale with a single electronic pulse represents a major step towards the future developments of ultrafast spintronic.…”
Section: Institut Jean Lamour Umr 7198 Cnrs -Université De Lorrainesupporting
confidence: 78%
“…Moreover, by replacing the [Co/Pt] layer by a GdFeCo layer, GdFeCo magnetization switching using ultrafast hot electron pulses and without direct light interaction was demonstrated [124]. These findings confirm the work reported by Wilson et al [125]. Therefore, switching the magnetization at the picosecond timescale with a single electronic pulse represents a major step towards the future developments of ultrafast spintronic.…”
Section: Institut Jean Lamour Umr 7198 Cnrs -Université De Lorrainesupporting
confidence: 78%
“…In a number of recent experiments [1][2][3][4][5][6][7][8] , it has been shown that femtosecond laser pulses can control magnetization on picosecond timescales, which is at least an order of magnitude faster compared to conventional magnetization dynamics. Among these demonstrations, the material system, GdFeCo ferrimagnetic films, is particularly interesting because deterministic toggleswitching of the magnetic order is possible without any external magnetic field.…”
Section: Main Textmentioning
confidence: 99%
“…We use the following exchange parameters for the interaction between spins located on the same sublattice A/B, J AA = 16 meV, J BB = 0.5 meV, and between spins on different sublattices, J AB = −6 meV. These values are characteristic for ferrimagnetic RE-transition metal (TM) alloys [59], which are testbed materials in the field of ultrafast spin dynamics [13][14][15][16][17], and are receiving an increasing attention in the field of spintronics [54].…”
Section: A Atomistic Spin Modelmentioning
confidence: 99%
“…We assume a lattice constant of a = 250 pm. Similar models have been already used in the literature to model the spin dynamics of ferrimagnetic systems, the most prominent example being GdFeCo alloys used for ultrafast toggle switching [13][14][15][16][18][19][20] and HD-AOS [25,29,30]. Despite their potential key role on such a switching process, the study of DW motion under thermal gradients of such kind of materials [6] has gained far less attention.…”
Section: A Atomistic Spin Modelmentioning
confidence: 99%
See 1 more Smart Citation